Foundations of Hegel's social theory : actualizing freedom - Neuhouser, Frederick (Harvard University Press, 2000)
"The author's purpose is to understand the philosophical foundations of Hegel's social theory by articulating the normative standards at work in his claim that the three central social institutions of the modern era--the nuclear family, civil society, and the constitutional state--are rational or good. Its central question is: what, for Hegel, makes a rational social order rational? In addressing this question the book aspires to be faithful to Hegel's texts and to articulate a compelling theory of rational social institutions; its aim is not only to interpret Hegel correctly but also to demonstrate the richness and power that his vision of the rational social order possesses."--